Oral Appearances in Patients with Diabetic Type I - F - Khozeimeh; GhH Mohseni (Isfahan University of Medical Sciences, 2005)
Introduction. Diabetes mellitus is a syndrome in which energy metabolism equilibrium is disturbed due to loss of secreted insulin or fault in it's function. The result is abnormal metabolim of carbohydrate protein and fat. Numerous oral soft tissue lesions were reported in diabetic patient. The goal of this study was to compare the relative frequency of oral manifestation in diabetic patients (type I) in diabetic research center with normal community of Isfahan.Methods. This experimental study was of case-control type. Popualation in which the study was conducted consisted of 96 diabetic patients and 96 healthy individuals who were relatives of diabetic patients accompanying them. Simple sampling method was used as the method of sampling Data were collected from research center by examining diabetic and control group. Data were then registeried in preformed check lists and statistically analyzed.Results. Data showed that relative frequency of irritation fibroma, fissure tongue, traumatic ulcers, xerostomia, glossodynia and candida related ulcer was 6.2, 21.9, 8.4, 57.3, 9.4 and 6.2 percent respectively. Their frequency in control group was 21, 9.4, 3.1, 16.6, 3.1 and 2.1 percent respectively.Discussion. There was statistically significant differences between frequency of these lesions and case control group. Comparing results of this study with the study of Guggenheim indicates that prevalence of these lesions in our case group was higher than his study group finally further study is suggested to determine the etiology of this high prevalence in our study group.Key words. Diabetes mellitus, Oral manifestations.